Editorial Vol. 12 Issue 1 - Kristy L Archuleta; Sarah D Asebedo (Journal of Financial Therapy, 2021)
We have exciting news to share with you in the Editorial Vol. 12 Issue 1! First we have an upcoming special issue on Diversity, Inclusion, and Equity that is slated to be published in December 2022. Second, but for the first time in JFT history, we are officially transitioning editors. We are excited for the future of the Journal of Financial Therapy. We hope you enjoy this issue.
Keywords: financial therapy